Numerical Methods for a Non-linear System Arising in Chemical Kinetics - Gumel, A. B.; Twizell, E. H.; Arigu, M. A.; Fakhir, F. (Universiti Putra Malaysia Press, 1997)
Two numerical methods are proposed for the solution of a system of two dimensional reaction-diffusion equations with cubic non-linearity, known as the "Brusselator" system. The first method is derived using finite difference techniques and the solution is obtained in paralled using two processors running concurrently. The second method is based on a predictor-eorrector technique. This system of equations has important applications in chemical kinetics.